Assessment for Identification of Stelechocarpus burahol and Sister Species Complex of Annonaceae Family Using trnL Intron Sequences - Probojati, Rasyadan Taufiq; Hadiyanti, Nugraheni; Hapsari, Lia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Stelechocarpus burahol (kepel) belongs to the Annonaceae family, and is considered to be a native species to Indonesia which is mainly distributed on the island of Java. However, the plant’s existence is currently difficult to find, so it is categorized as rare in Indonesia. A molecular approach using DNA barcoding technique is significant to assist plant identification. The gene that is widely used and proven to be accurate for Annonaceae is trnL-F. This study was aimed to evaluate the efficiency of trnL as DNA barcode for the identification of S. burahol and its relatives (Annonaceae) from Java Island. In total 10 specimens have been used in this study. Whole genome DNA was isolated by Tiangen kit and amplified by Polymerase Chain Reaction (PCR) technique using a specific primer. Results showed that trnL was easily amplified with a DNA fragment length of 500-600 bp. The trnL amplicons have successfully sequenced as indicated by the high QV20+ values. The sequence compositions were high in AT bases (63.9%). BLAST analysis of the sequences showed that S. burahol and sister species have been confirmed its identity according to the reference sequences in NCBI with query cover identities 98%-100%. This research can be concluded that trnL-F is suitable and recommended as a DNA barcode for S. burahol and its relatives. However, further research is suggested to combine analysis of both coding (rbcL, matK, etc) and non-coding (trnL) markers for better identification results.